Potent in vitro anti-proliferative, apoptotic and anti-oxidative activities of semi-purified Job's tears (Coix lachryma-jobi Linn.) extracts from different preparation methods on 5 human cancer cell lines - Manosroi A. (2017)
© 2016 Elsevier Ireland Ltd. All rights reserved. Ethonopharmacological relevances Job's tears (Coix lacryma-jobi Linn.) is commonly used as an herbal medicine. The low incidence of cancer has been observed in the area of China where regularly consume Job's tears. The effects of preparation methods of Job's tears on anti-cancer activities were investigated. Potent in vitro anti-proliferative, apoptotic and anti-oxidative activities of semi-purified Job's tears extracts from different preparation methods on 5 human cancer cell lines comparing with standards and commercial product were observed. Aim of study To study the anti-proliferative, apoptotic and anti-oxidative activities of semi-purified Job's tear extracts from different preparation methods on 5 human cancer cell lines. Materials and methods The crude methanolic extracts of non-cooked, steamed and roasted Job's tears cultivars were prepared and further semi-purified by liquid-liquid extraction techniques. Both of crude and semi-purified extracts were tested for anti-proliferative, apoptotic induction, anti-oxidative activities and phytochemicals content. Results The highest yields of crude and-purified extracts were 4.60% and 1.46%, respectively. In crude extracts, the steamed whole Thai Black Loei Job's tears (W-TBL-S1) extract showed the highest anti-proliferative activity in mouth epidermal carcinoma cell (KB) at the IC 50 of 43.61±0.76 μg/ml (0.005 folds of doxorubicin), whereas the roasted whole Laos White Loei Job's tears (W-LWL-R2) extract showed the highest apoptotic activity in cervical adenocarcinoma (HeLa) at 21.52±1.50% (0.22 and 15.05 folds of doxorubicin and commercial product, respectively). After liquid-liquid extraction, almost all of the semi-purified extracts showed increases in anti-proliferative activity. Ethyl acetate fraction of the roasted whole Laos White Loei Job's tears (W-LWL-R2) showed the highest anti-proliferative activity in HeLa cell at the IC 50 of 0.97±0.82 μg/ml (7.82 and 45.39 folds of doxorubicin and crude extract, respectively) and apoptotic activity of 18.77±6.31% (0.19 folds of doxorubicin). The commercial product showed no anti-proliferative activity in all cell lines but induced apoptosis in HeLa cell at 1.43±0.34%. The butanol and hexane soluble fractions of the roasted whole of Laos White Loei Job's tears (W-LWL-R2) showed the highest free radical scavenging (SC 50 ) and metal chelating activity (MC 50 ) of 0.31±0.06 mg/ml (0.64 folds of ascorbic acid) and 0.08±0.01 mg/ml (6.37 folds of EDTA), respectively. All ethyl acetate fractions contain high content of carotenoid and tannin, whereas the hexane soluble fraction of the roasted hull of Laos Black Loei Job's tears (H-LBL-R1) showed the highest linoleic acid content of 8.09±0.74% w/w. Conclusions This study has demonstrated the potent anti-cancer activity of the semi-purified extracts from roasted Job's tears with high potential for further development to modern anti-cancer drug.